Effects of acupuncture on gastrointestinal diseases and its underlying mechanism: a literature review of animal studies - Kim, Min-Joon; Lee, Seri; Kim, Seung-Nam (Frontiers in Medicine, 2023)
Acupuncture is a non-pharmacological traditional Chinese medical technique that has been used for various types of gastrointestinal (GI) diseases in Eastern medicine. However, the specific mechanisms underlying acupuncture treatment in the GI tract have not yet been elucidated. In this study, we searched the electronic databases PUBMED, EMBASE, and MEDLINE and identified 30 eligible studies that were summarized in this review. This review demonstrates that treatments, including both manual and electroacupuncture, have therapeutic mechanisms in diverse GI diseases. The underlying mechanisms are broadly divided into the following: changes in gene expression in the gastric mucosa or nuclei of the solitary tract, metabolic change induction, regulation of anti-inflammatory substances, vagal activity increase, change in functional connectivity between brain regions, and control of the number of neurons related to GI diseases. Although this study is limited in that it does not represent all types of GI diseases with different acupuncture methods, this study identified acupuncture as effective for GI diseases through various biological mechanisms. We hope that our study will reveal various mechanisms of acupuncture in GI diseases and play an important role in the therapy and treatment of GI diseases, thus advancing the field of study.